Insect Vectors of Rice Yellow Mottle Virus. (2nd February 2015) - Koudamiloro, Augustin; Nwilene, Francis Eegbara; Togola, Abou; Akogbeto, Martin
Abstract : Rice yellow mottle virus (RYMV) is the major viral constraint to rice production in Africa. RYMV was first identified in 1966 in Kenya and then later in most African countries where rice is grown. Several studies have been conducted so far on its evolution, pathogenicity, resistance genes, and especially its dissemination by insects. Many of these studies showed that, among RYMV vectors, insects especially leaf-feeders found in rice fields are the major source of virus transmission. Many studies have shown that the virus is vectored by several insect species in a process of a first ingestion of leaf material and subsequent transmission in following feedings. About forty insect species were identified as vectors of RYMV since 1970 up to now. They were essentially the beetles, grasshoppers, and the leafhoppers. For this review, we presented the chronology of their identification. Also, the biology, ecology, host range, distribution, and caused damage of these insects were briefly summarized.